From wet nurses to Ismálias deprived of parental authority:an intersectional analysis - Rocha, Andréa Pires; Procópio, Alice Justo (Argumentum, 2025)
This paper presents the results of a qualitative study analysing the profile of women who lost parental authority in a judicial district of a large municipality in the northern region of the state of Paraná, Brazil. The research combines literature review with documentary analysis, based on the examination of seven judicial cases followed by the Social Work service of the Juvenile Court, between August 2023 and August 2024. The analysis revealed a convergence of race/skin colour, social class, gender, and abusive use of psychoactive substances in the profiles of the women affected. The termination of parental authority operates selectively on Black and poor women, exposing the role of a punitive State embedded in punitive neoliberalism, and grounded in structural racism and patriarchy, which shifts the absence of public care policies into the moral blaming of women.
Keywords: Termination of parental authority; Structural racism; Intersectionality